Analisis Drug Related Problems (DRPs) Pada Pasien Angina Pektoris RS X Kota Cirebon Tahun 2023 - Efriani, Like; Irawan, Ade; Anwar, Mahfud (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2024)
Angina pectoris is one symptoms of heart disease that is a problem and a major trigger of death in Indonesia characterized by chest pain. The prevalence of angina increases every year due to various risk factors such as age, lifestyle and history diseases such as diabetes, cholesterol, and hypertension. Use of drugs in large is at risk of drug-related problems. Drug Related Problems (DRPs) are medication problems that directly or indirectly affect the results of prescribed therapy. The purpose of this study was to analyze the incidence of actual or potential DRPs in patients angina pectoris. This research is observational non-experimental. Data collection was taken from 66 medical records of angina pectoris patients from January to December 2023 who met the inclusion criteria. The incidence of DRPs was analyzed by qualitative descriptive method based on the literature. The results of the analysis showed DRPs occurred in 61 (92%) hospitalized angina pectoris patients. The presence of DRPs in the category of drug interactions (60.77%), duplication of drug groups (20.26%), underdose (12.05%), overdose (5.13%), and inappropriate drugs (1.79%). The results of the analysis did not show a significant relationship between comorbidities and polyphamidation to DRPs. It can be concluded that the incidence of DRPs in hospitalized angina pectoris patients is quite large (92%), requiring the role of pharmacists in preventing and overcoming DRPs.